Causes of Unwillingness to Childbearing in Families Visiting Urban and Rural Health Centers in Northwest Iran - Leila Parandeh; Roghayeh Khabiri; Ali Nayerpour; Baqer Safa; Jila Khalkhali (Taṣvīr-i salāmat, 2025)
Background. Childbearing significantly affects the population's composition and age structure. The decline in fertility rates will disrupt the age balance of the country's population, leading to irreparable economic and social damage. This study investigates the causes of reluctance to engage in childbearing in Shabestar, Iran. Methods. This cross-sectional, descriptive-analytical study included 346 individuals using a random sampling method. A researcher-made questionnaire containing two parts was used to collect the required data. The first part of the questionnaire included demographic information. The second part was the childbearing desire questionnaire (specially designed for married men and women), each containing 17 items related to independent variables. Results. The results obtained from the logistic regression test showed that there was a statistically significant relationship between the economic problems of the family, lack of mental and emotional preparation for having children , worry about preparing a promising future for children, inability to raise children, inappropriate age for pregnancy and reluctance to have children. Moreover, participants mentioned reasons like lack of psychological readiness to have a child (67.05% of the participants), increasing economic problems with having children (65.90% of the participants), not having enough income to have children (65.32% of the participants), among others, for unwillingness to childbearing. Conclusion. To promote childbearing, addressing the economic problems of families should be a priority in national policymaking. In addition, various educational and supportive methods can reduce insecurity in young families and bring the fertility rate to the desired level.